PERICARDIAL EFFUSION IN HIV-INFECTED PATIENT - E. V. Filippov; S. S. Yakushin; N. V. Zaytseva; L. G. Tokareva; G. O. Ivanova (Klinicist)
Incidence of cardiovascular events among HIV-infected patients in clinical practice has increased recently. Usually strategy of treatment in such patients differs from the conventional and requires close cooperation with experts in HIV infection. Example of successful treatment of the acute pericardial effusion in patient with stage III HIV (World Health Organizationclassification) is presented in this clinical case.